Pelanggaran Maksim Prinsip Kesantunan Debat Dua Sisi Tv One - Oktavia, Nia; Hermaliza, Hermaliza (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
The principle of the politeness must be applied in communicating when speaking with the interlocutor. But many people do not show this or do not comply with the principle of politeness so that they are said to have violated the principle of politeness. Research method, namely the method of content analysis. The results of this study are 1) the violation of maxim wisdom is 13 utterances out of 50 utterances, 2) the violation of the maxim of acceptance is 1 utterances out of 50 utterances, 3) the violation of the maxim of generosity is 7 utterances out of 50 utterances, 4) the violation of the maxim of humility is 8 utterances out of 50 utterances, 5) the violation of the maxim compatibility is 21 utterances out of 50 utterances, 6) the violation of the maxim of sympathy is 0 utterances out of 50 utterances.